2D-structured V-doped Ni(Co, Fe) phosphides with enhanced charge transfer and reactive sites for highly efficient overall water splitting electrocatalysts. Issue 20 (13th May 2021) - Jeung, Yongjae; Jung, Hyeonjung; Kim, Dokyoung; Roh, Hyogyun; Lim, Chaeeun; Han, Jeong Woo; Yong, Kijung
Abstract : 2D Ni-based transition metal phosphide catalysts could exhibit improved overall water splitting performance through vanadium doping which increases the electrical conductivity and controls catalyst's adsorption energy with water. Abstract : 2-D Ni alloy phosphide catalysts are of great interest due to their strong bond strength to reaction intermediates and numerous active sites for alkaline overall water splitting (OWS) reactions. However, the limitations of hydrogen evolution reaction (HER) activity and electrical conductivity significantly lower the OWS activity compared to noble metal catalysts. To overcome this problem, V-doping of 2D Ni(Co, Fe) phosphide was performed to increase the electrical conductivity and catalytic activity by tuning the electron density of the active sites. The synthesized NiCoVP had a low Tafel slope of 30 mV dec −1 and a reduced overpotential of 42 mV compared to NiCoP (75 mV), which has high stability as an alkaline HER catalyst, yielding 10 mA cm −2 . The charge transfer resistance also decreased from 8.8 Ω (NiCoP) to 7.1 Ω (NiCoVP). As an alkaline oxygen evolution reaction (OER) catalyst, NiFeVP showed a low overpotential of 234 mV to generate 10 mA cm −2 compared to NiFeP (249 mV) with a Tafel slope of 34.4 mV dec −1 . V doping reduced the charge transfer resistance from 3.6 Ω (NiFeP) to 1.2 Ω (NiFeVP). The OWS system combining NiCoVP–NiFeVP required 1.50 V for 10 mA cm −2, which is the lowest among the transition metal-based phosphide catalysts reported so far. This marked improvement in alkaline OWS activity through V doping was also proven by the density functional theory (DFT) calculation results of high affinity to *OH, which enhances water dissociation for the HER and strong metal–O covalence bonds for the OER.